Osteogenic Differentiation of Human Amniotic Fluid–derived Stem Cells Induced by Bone Morphogenetic Protein-7 and Enhanced by Nanofibrous Scaffolds - Sun, Hongli (2009)
Amniotic fluid–derived stem cells (AFSCs) are becoming an important source of cells for regenerative medicine given their apparent advantages of accessibility, renewal capacity and multipotentiality. In the intermediate stage between the embryonic stem cells (ESCs) and adult stem cells, AFSCs may have a distinct mechanism to choose their fate. Unfortunately, until now, little is known about how bone morphogenetic proteins (BMPs) control the osteoblastic differentiation of AFSCs, especially on 3D scaffolds. Our research shows that human AFSCs (hAFSCs) can be induced for osteoblastic differentiation by rhBMP-7, and hAFSCs respond to rhBMP-7 more strongly than human mesenchymal stem cells (hMSCs). As synthetic ECM, scaffolds play a central role in tissue engineering. The hAFSCs, on the nanofibrous scaffolds (NF scaffolds) with morphology similar to that of natural collagen fibers, showed significantly enhanced alkaline phosphatase (ALP) activity, calcium content, von Kossa staining and the expression of osteogenic genes than those on the traditional scaffolds, i.e. solid walled scaffolds. The data on the bone formation in vivo presented further evidence that biomimetic NF scaffolds provided hAFSCs a more favorable synthetic ECM, and thus, facilitated the osteogenic differentiation of hAFSCs. The relative strong responsiveness to rhBMP-7 makes hAFSCs promising in bone regeneration. The synthetic NF scaffolds, which mimic the morphology of natural collagen fibers, enhanced the osteoblastic differentiation of hAFSCs in vitro and bone formation in vivo.